ARUS KAS, KOMITE AUDIT DAN MANAJEMEN LABA STUDI KAUSALITAS PADA PERUSAHAAN MANUFAKTUR INDONESIA - Cut Nessa Cinthya; Mirna Indriani (Jurnal Dinamika Akuntansi dan Bisnis, 2015)
AbstractThis study aims to examine the influence of free cash flow, audit committees for earning managemen by using discretionary accruals as a proxy of earning management. The samples of this research were the manufacturing firms listed in BEI (Indonesia Stock Exchange) between 2010 and 2014. The samples wereselectedby using purposive sampling on 52 companies with 260 observations. The Data were collected from annual report and data analyzed by multiple regression analysis.The results of this study shows that free cash flow has negative influence for earnings management, size of audit committee has no influence for earnings management, and the number of audit committee meetings has negative influence for earnings management. Keywords: Free Cash Flow, Size of Audit Committee, Number of Audit Committee Meeting, Earnings Management.